The Interleukin-10 Family of Cytokines and Their Role in the CNS - Burmeister, Amanda R.; Marriott, Ian (Frontiers in Cellular Neuroscience, 2018)
Resident cells of the central nervous system (CNS) play an important role in detecting insults and initiating protective or sometimes detrimental host immunity. At peripheral sites, immune responses follow a biphasic course with the rapid, but transient, production of inflammatory mediators giving way to the delayed release of factors that promote resolution and repair. Within the CNS, it is well known that glial cells contribute to the onset and progression of neuroinflammation, but it is only now becoming apparent that microglia and astrocytes also play an important role in producing and responding to immunosuppressive factors that serve to limit the detrimental effects of such responses. Interleukin (IL-) 10 is generally considered to be the quintessential immunosuppressive cytokine, and its ability to resolve inflammation and promote wound repair at peripheral sites is well documented. In the present review, we discuss the evidence for the production of IL-10 by glia, and describe the ability of CNS cells, including microglia and astrocytes, to respond to this suppressive factor. Furthermore, we review the literature for the expression of other members of the IL-10 cytokine family, IL-19, IL-20, IL-22, and IL-24, within the brain, and discuss the evidence of a role for these poorly understood cytokines in the regulation of infectious and sterile neuroinflammation. In concert, the available data indicate that glia can produce IL-10 and the related cytokines IL-19 and IL-24 in a delayed manner, and these cytokines can limit glial inflammatory responses and/or provide protection against CNS insult. However, the roles of other IL-10 family members within the CNS remain unclear, with IL-20 appearing to act as a pro-inflammatory factor, while IL-22 may play a protective role in some instances and a detrimental role in others, perhaps reflecting the pleiotropic nature of this cytokine family. What is clear is that our current understanding of the role of IL-10 and related cytokines within the CNS is limited at best, and further research is required to define the actions of this understudied family in inflammatory brain disorders.